The Effect of Lecturer Competence in Online Learning Methods on Student College Satisfaction During the Pandemic - Asty Khairi Inayah Syahwani; Annisaa Soeyono (Universitas Muhammadiyah Sidoarjo, 2021)
The first quarter of 2020 has been a difficult time for the global community. The Coronavirus (COVID-19) pandemic is affecting various sectors, one of which is education. Physical distancing policies allow learning to be done remotely. Based on the conditions of distance learning, this study wanted to determine the effect of lecturer co mpetence on student satisfaction during a pandemic. The data was collected by distributing questionnaires to college students using purpose sampling. Data analysis using SEM-PLS method. The results showed that social and personality competence had an effect on student satisfaction, but lecturers' pedagogical and professional competence had no effect on student satisfaction during the pandemic. This can be shown from the inadequate infrastructure of distance learning. Lecturers who are needed now are lecturers who have the power of creativity in delivering material so that the delivery of material to students is more interesting and varied in online learning.